2019
DOI: 10.1021/acs.inorgchem.8b03363
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Assisted Chemical Vapor Deposition of ZnS from Thioureide Single Source Precursors

Abstract: A family of 12 zinc(II) thoureide complexes, of the general form [{L}ZnMe], [{L}Zn{N(SiMe 3 ) 2 }], and [{L} 2 Zn], have been synthesized by direct reaction of the thiourea pro-ligands i PrN(H)CS(NMe 2 ) H[L 1 ], CyN(H)CS(NMe 2 ) H[L 3 ], t BuN(H)CS(NMe 2 ) H[L 2 ], and MesN(H)CS(NMe 2 ) H[L 4 ] with either ZnMe 2 (1:1) or Zn{N(SiMe 3 ) 2 } 2 (1:1 and 2:1) and characterized by elemental analysis, NMR spectroscopy, and thermogravimetric analysis (TGA). The molecular structures of complexes [{L 1 9), and [{L 4 }… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Both structures are analogous to each other and also to reported methyl zinc thioureides, with dimerization occurring through S atoms and formation of a Zn–S–Zn–S ring structure. 30 The C–S bond in 2 was significantly lengthened as compared to the free ligand HL 1 * (1.7678(16) Å and 1.6852(15) Å respectively) whilst the C–N(Ph) bond was shortened (1.323(2) Å and 1.3715(18) Å) upon coordination to the zinc centre. The C–N(Me 2 ) bond in HL 1 * was also significantly shorter than in 2 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Both structures are analogous to each other and also to reported methyl zinc thioureides, with dimerization occurring through S atoms and formation of a Zn–S–Zn–S ring structure. 30 The C–S bond in 2 was significantly lengthened as compared to the free ligand HL 1 * (1.7678(16) Å and 1.6852(15) Å respectively) whilst the C–N(Ph) bond was shortened (1.323(2) Å and 1.3715(18) Å) upon coordination to the zinc centre. The C–N(Me 2 ) bond in HL 1 * was also significantly shorter than in 2 .…”
Section: Resultsmentioning
confidence: 97%
“…Taking inspiration from Sullivan et al , 30 thiourea ligands were chosen as the sulfur source due to their facile, high yielding synthesis which circumvents issues with usage of H 2 S gas and other malodourous sulfur containing compounds. Their work also showed that zinc thioureides were effective SSPs towards phase pure zinc sulfide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the complexes dimerise analogously, with dative interactions between the zinc atom on one monomeric unit and the methine carbon on the ligand of the second monomeric unit ( Figure 3 ). This dimerisation is uncommon in zinc alkyl complexes, with most dimerisation occurring through a [Zn–L] 2 (L = donor atom) ring interaction ( Figure 3 , left) [ 21 , 22 , 23 , 24 ]. A bis (N-heterocyclic carbene) zinc ethyl complex previously reported dimerises in a similar fashion to 1 and 2 , though this was due to the unusual deprotonation of the methylene proton of the ligand backbone by diethylzinc, and the formation of a formal Zn–C bond ( Figure 3 , right) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%